Comparison of left ventricular volumes and ejection fraction by monoplane cineventriculography, unenhanced echocardiography and cardiac magnetic resonance imaging - Li, Chunjian; Loßnitzer, Dirk; Katus, Hugo; Buß, Sebastian Johannes (The international journal of cardiovascular imaging, 2012)
Right-anterior-oblique (RAO) monoplane cineventriculography is usually applied in cardiac catheter labs to assess the left ventricular (LV) function. However, it is uncertain whether this technique is reliable in clinical routine. Unenhanced two-dimensional echocardiography was reported to underestimate left ventricular volumes. The aim of this study was to compare these two conventional techniques with cardiac magnetic resonance imaging (MRI), the present gold standard for the determination of LV function, to evaluate whether the results from the conventional techniques are reliable and in accordance with each other. Seventy-two patients were retrospectively recruited and analysis of the three techniques was performed. Compared with MRI, RAO cineventriculography underestimated LV end-systolic volumes (ESV), and overestimated LV ejection fraction (EF); two-dimensional echocardiography underestimated LV end-diastolic volume (EDV) and EF. Correlation coefficients on EDV, ESV, and EF were 0.8806, 0.9201, and 0.8864 between echocardiography and MRI (P < 0.01, for all), followed by 0.7718, 0.8835, and 0.7785, between cineventriculography and MRI (P < 0.01, for all), and 0.7006, 0.7680, and 0.7644 between cineventriculography and echocardiography (P < 0.01, for all). Echocardiography and MRI showed the highest inter-technique correlation coefficients, and the narrowest Bland-Altman limits of agreement for EDV, ESV and EF. EDV, ESV and EF determined by RAO monoplane cineventriculography, unenhanced two-dimensional echocardiography and MRI were in high accordance with each other, with wide variances between the techniques. Although not interchangeable, RAO monoplane cineventriculography, unenhanced two-dimensional echocardiography, and cardiac MRI are reliable tools in clinical routine for the assessment of LV volumes and function.